Fruit juice drinks prevent endogenous antioxidant response to high-fat meal ingestion. Issue 2 (28th January 2014) - Miglio, Cristiana; Peluso, Ilaria; Raguzzini, Anna; Villaño, Deborah V.; Cesqui, Eleonora; Catasta, Giovina; Toti, Elisabetta; Serafini, Mauro
<x content-type="archive" xml:space="preserve">Abstract</x> High-fat meals (HFM) induce metabolic stress, leading to the activation of protective mechanisms, including inflammation and endogenous antioxidant defences. In the present study, we investigated the effects of antioxidant-rich fruit juice drinks on the endogenous antioxidant response induced by HFM. In a double-blind, cross-over design (10 d washout), fourteen overweight volunteers were randomly assigned to one of the following interventions: HFM+500 ml placebo beverage (HFM-PB, free from fruit); HFM+500 ml antioxidant beverage 1 (HFM-AB1; apple, grape, blueberry and pomegranate juices and grape skin, grape seed and green tea extracts); HFM+500 ml antioxidant beverage 2 (HFM-AB2; pineapple, black currant and plum juices). HFM-PB consumption increased the plasma levels of thiols (SH) (4 h, P< 0·001) and uric acid (UA) (2 h, P< 0·01) and total radical-trapping antioxidant parameter (TRAP) (4 h, P< 0·01). Following the consumption of drinks, UA production was significantly reduced with respect to placebo beverage consumption 8 h after HFM-AB2 consumption (P< 0·05). SH levels were reduced 0·5 (P< 0·05), 1 (P< 0·05) and 2 h (P< 0·01) after HFM-AB1 consumption and 2, 4 and 8 h (P< 0·05) after HFM-AB2 consumption. Plasma TRAP (2 h, P< 0·001) and urinary ferric reducing antioxidant power (0–8 h, P< 0·01) were increased by HFM-AB1 consumption, the drink with the highest in vitro antioxidant capacity, but not by HFM-AB2 consumption. In urine, UA levels were significantly increased from basal levels after the consumption of HFM-PB and HFM-AB2. However, neither of the beverages increased the urinary excretion of UA with respect to the placebo beverage. In conclusion, the increase in UA and SH levels induced by HFM as part of an endogenous antioxidant response to postprandial stress can be prevented by the concomitant ingestion of antioxidant-rich fruit juice drinks.